Temporary Worker Programs as Precarious Status - Goldring, Luin (Canadian Issues, 2010)
Temporary foreign worker programs have been both passionately criticized and applauded. They have been analyzed from multiple stakeholder perspectives - employers, workers, governments and unions - and in relation to various thematic arenas, including labour markets, employment standards, communities, health, and so on (see other authors in this issue). The implications of temporary workers and these programs for rights and citizenship have also been taken up (Basok 1999 and 2002, Preibisch 2004, Sharma 2006, Bauder 2007), although such discussions circulate less widely than those focused on employment. My purpose here is to situate temporary worker programs in relation to the concept of precarious status in order to contribute to discussions regarding citizenship and nation building - where the latter invokes questions about political community, rights, bases for membership, and belonging. I make a two-fold argument: 1 ) that temporary worker programs should be understood as one of several elements of policy practice that contribute to precarious status in Canada; and 2) that the connection between precarious status and citizenship needs to be analyzed and debated because it has important implications for citizenship and nation building in Canada. Since the 1970s, Canadian immigration and citizenship policy has selected immigrants and focused on supporting their transition to settled citizens, creating a nation where membership is framed in civic and multicultural terms. Recent policy shifts establish a two-tier system, with settled residents and citizens and an array of presumably temporary "others ."At the heart of the matter is whether Canada wants to pursue immigration and citizenship policies that entrench legal exclusion and cUscrimination based on migratory status, and potentially erode rights for all by virtue of reducing or eliminating them for some, or whether Canadians want to develop policies and strategies that provide alternatives, such as expanding social, civil and perhaps political rights for non-citizens, as well as earlier and more effective pathways to citizenship. Debating these issues can contribute to the ongoing process of defining and negotiating Canadian identities, values and norms as well as policies designed to expand social inclusion - for citizens as well as non -citizens in Canada. The discussion is organized into three sections. The first defines precarious status. The second situates temporary worker programs as contributing to a form of precarious status. The third section outlines and discusses implications of precarious status for citizenship, inclusion and nation building. Temporary entrance categories and the growth of precarious status. Forms of precarious status associated with temporary entrance categories are likely to persist and increase through two mechanisms: 1) as a continuation of the increase in temporary entries as well as the number of temporary residents present in Canada. The current economic crisis may put a dent in the admission of temporary workers (Galloway 2009), but this is unlikely to alter their long-term increase;7 and 2) through movement from authorized to unauthorized precarious statuses. It is possible to transition from temporary status to permanent resident status, as when foreign students or refugee claimants become permanent residents. This possibility is, however, extremely limited for most temporary workers; exceptions include those in the Live- in Caregiver Program and the recently created Canadian Experience Class, as well as through the Provincial Nominee Program, which has been used as a pathway to permanent residence for small numbers of workers in some provinces ([Elgersma] 2007, Byel 2007). What is also possible is movement from authorized to unauthorized precarious status. However, there are no systematic data relative to overstaying for the temporary resident category.
Keywords: Citizenship; Foreign labor; Humanities: Comprehensive Works; Immigration policy; Social Sciences: Comprehensive Works; Studies; Temporary employment